2007
DOI: 10.2174/157018007780077381
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Acidic CCR2 Receptor Antagonists: From Hit to Lead

Abstract: High throughput screening identified a pyrrolidinone containing acidic functionality as a CCR2 antagonist of modest affinity. We describe initial SAR around this hit, including solution phase parallel synthesis for analog preparation, and we describe identification and characterization of an analog subsequently selected as a viable lead molecule for further optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…All antagonists displaced 125 I-CCL2 from the receptor ( Fig. 3A; Table 2) with affinities similar to previously reported data (Mirzadegan et al, 2000;Brodmerkel et al, 2005;Zou et al, 2007;Buntinx et al, 2008;Cherney et al, 2008;Moree et al, 2008). BMS22, RS504393, and Teijin were also able to displace (Table 2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All antagonists displaced 125 I-CCL2 from the receptor ( Fig. 3A; Table 2) with affinities similar to previously reported data (Mirzadegan et al, 2000;Brodmerkel et al, 2005;Zou et al, 2007;Buntinx et al, 2008;Cherney et al, 2008;Moree et al, 2008). BMS22, RS504393, and Teijin were also able to displace (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…INCB3344, JNJ-27141491, and CCR2-RA- [R] were synthesized in-house as described previously (Xue et al, 2004;Brodmerkel et al, 2005;Zou et al, 2007;Doyon et al, 2008 …”
Section: Methodsmentioning
confidence: 99%
“…Substitution of the cycloalkyl group by a phenyl group ( 9 ) led to a great loss of CCR2 affinity (39% displacement at 1 μM), consistent with previously reported values showing a decreased affinity for an almost similar pair of compounds. 36 Yet this substitution only led to a 3-fold decrease in CCR1 affinity ( K i of 162 nM), thus showing much higher selectivity for CCR1. Next, we explored the effect of N -aryl modifications in both affinity and selectivity (compounds 10 – 17 ), specifically the effect of para and meta substituents.…”
Section: Resultsmentioning
confidence: 97%
“…Previous modifications to the vinylogous carboxylic acid functionality in CCR2 showed detrimental effects in binding affinity. 29,36 Indeed, mutagenesis and structural studies have shown crucial interactions of the hydroxyl and the two carbonyl groups with Glu310 8x48 , Lys311 8x49 , and Phe312 8x50 (residues according to structure-based Ballesteros–Weinstein numbering 37 ) in CCR2. 24,28 Sequence alignment of CCR1 and CCR2 (Supporting Information, Figure S2) and our docking study (Figure 2) suggest similar interactions in CCR1, as only position 8.49 differs (arginine in CCR1 and lysine in CCR2).…”
Section: Resultsmentioning
confidence: 99%
“…CCL2 was purchased from PeproTech (Rocky Hill, NJ). INCB3344, JNJ-27141491, and CCR2-RA- [R] were synthesized according to published methods (Xue et al, 2004;Brodmerkel et al, 2005;Zou et al, 2007;Doyon et al, 2008). SD-24 (sulfonamide derivative #24 from Peace et al, 2010) was synthesized in-house, according to procedures described previously (Peace et al, 2010 CCR5 was cloned in-house from a leukocyte cDNA library, whereas WT FLAG-tagged CCR2 cDNA was kindly provided by Dr. Tim Wells (GlaxoSmithKline, London, UK).…”
Section: Methodsmentioning
confidence: 99%